2008
DOI: 10.1029/2007jb005170
|View full text |Cite
|
Sign up to set email alerts
|

Regional structure and kinematic history of a large subduction back thrust: Taranaki Fault, New Zealand

Abstract: The Taranaki Fault is a back thrust antithetic to the Hikurangi margin subduction thrust. Subduction back thrusts, like the Taranaki Fault, accrue displacement transferred from the subducting plate, and growth analyses of these structures contribute to an improved understanding of subduction processes. The Taranaki Fault forms the eastern margin of the Taranaki Basin and is part of a system that extends for at least 600 km in continental crust of western New Zealand. The fault is preserved beneath young sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(155 citation statements)
references
References 58 publications
7
147
1
Order By: Relevance
“…Most of the basin remained tectonically quiescent till the end of the Eocene. However, it is also observed that an overall pattern of asymmetric eastward thickening of Middle to Late Eocene strata suggests regional fault-controlled subsidence during this period (Stagpoole and Nicol 2008). Major formations within the field have low regional dip angle (~ 10°) in the north and (~ 15°) in the southern part of the field (Haque et al 2016).…”
Section: Regional Geological Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the basin remained tectonically quiescent till the end of the Eocene. However, it is also observed that an overall pattern of asymmetric eastward thickening of Middle to Late Eocene strata suggests regional fault-controlled subsidence during this period (Stagpoole and Nicol 2008). Major formations within the field have low regional dip angle (~ 10°) in the north and (~ 15°) in the southern part of the field (Haque et al 2016).…”
Section: Regional Geological Settingsmentioning
confidence: 99%
“…Taranaki Basin is the largest basin of New Zealand which is overprinted by Neogene convergent margin-related tectonics (Stagpoole and Nicol 2008;King and Thrasher 1992;King 1990). The entire New Zealand subcontinent is characterized by a passive margin and subsidence followed by consecutive accumulation of Paleocene-Eocene sediments across the shelfal and coastal plains of the basin (King 1990).…”
Section: Regional Geological Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seismic-stratigraphic evidence shows that the New Caledonia Trough either formed or was substantially modified during this event, though Cretaceous sedimentary basins beneath the trough escaped Cenozoic convergent deformation in most places (Collot et al, 2008;Sutherland et al, 2010). Regional deformation and emplacement of allochthons in northern New Zealand occurred later than in New Caledonia or the Norfolk Ridge system, with the onset of tectonic activity during the late Oligocene and early Miocene (~30-20 Ma) (Bache et al, 2012;Herzer, 1995;Herzer et al, 1997;Rait et al, 1991;Stagpoole and Nicol, 2008).…”
Section: Geological Settingmentioning
confidence: 99%
“…For instance, the Taranaki Fault in the northern part of New Zealand is considered to be a back thrust antithetic to the Hikurangi margin subduction thrusts. The Taranaki Fault has accommodated at least 12-15 km of dip-slip displacement since the middle Eocene (~40-43 Ma) (e.g., Stern et al 2006;Nicol et al 2007;Stagpoole and Nicol 2008).…”
Section: Tectonic Implication Of the Low-angle Southward-dipping Thrustmentioning
confidence: 99%